Is contact between men who have sex with men and non‐governmental organizations providing harm reduction associated with improved HIV outcomes?. Issue 4 (12th November 2020) - Trickey, A; Stone, J; Semchuk, N; Saliuk, T; Sazonova, Y; Varetska, O; Lim, AG; Walker, JG; Vickerman, P
Abstract : Objectives: There is a high prevalence of HIV (5.2% in 2018) among men who have sex with men (MSM) in Ukraine. HIV testing, condom provision and facilitated linkage to HIV treatment have been funded by various bodies through non‐governmental organizations (NGOs). We investigated whether contact with these NGOs was associated with improved prevention and treatment outcomes among MSM in Ukraine. Methods: Data were taken from four rounds of integrated bio‐behavioural surveys among MSM in Ukraine (2011,   N  = 5950; 2013,   N  = 8101; 2015,   N  = 4550; 2018,   N  = 5971) including HIV testing combined with questionnaire responses. Data were analysed using mixed‐effect regression models, which estimated associations between being an NGO client and behavioural, HIV testing and HIV treatment outcomes, adjusted for demographic factors. Results: Those MSM who were NGO clients were more likely than non‐clients to have been HIV tested in the last year [adjusted odds ratio (aOR) = 7.01, 95% confidence interval (CI): 6.45–7.62] or ever (aOR = 11.00, 95% CI: 9.77–12.38), to have used a condom for the last anal sex act (aOR = 1.32, 95% CI: 1.21–1.43), and to have recently either bought or received condoms (aOR = 21.27, 95% CI: 18.01–25.12). HIV‐positive MSM were more likely to have contact with NGOs (aOR = 1.61, 95% CI: 1.39–1.86). Among the HIV‐positive MSM, those who were NGO clients were more likely to be registered at an AIDS centre (aOR = 2.24, 95% CI: 1.61–3.11) and to be on antiretroviral treatment (aOR = 2.20, 95% CI: 1.51–3.20). Conclusions: In Ukraine, being in contact with MSM‐targeted NGOs is associated with better outcomes for HIV prevention, testing and treatment, suggesting that NGO harm reduction projects for MSM have had a beneficial impact on reducing HIV transmission and morbidity.